Peran Smart City dalam Pengelolaan Lingkungan Perkotaan: Studi Kasus Implementasi di Kota Bandar Lampung - Shinta Riana Putri; Erlin Kurniati (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
The Smart City concept is viewed as an innovative answer to the urgent need for sustainable urban environment management. In this context, the city of Bandar Lampung, which is one of the developing cities in Indonesia, has begun to integrate various technologies with the primary goal of increasing efficiency in environmental management. This research specifically focuses on an in-depth analysis of the implementation of the Smart City concept in the context of environmental management in the city of Bandar Lampung. In addition, this research also aims to identify the challenges that may arise during the implementation process, as well as the opportunities that can be utilized to optimize these efforts. The research method applied in this study is a case study with a qualitative approach, which involves the use of a comprehensive set of data collection techniques. These techniques include direct field observations to obtain an in-depth understanding of real field conditions, in-depth interviews with relevant stakeholders to gain diverse perspectives, and analysis of relevant policy documents that serve as the theoretical basis and implementation framework. The results of this study reveal that the implementation of Smart City-based technology in Bandar Lampung has begun to be implemented in various sectors. These sectors include digital-based waste management to improve efficiency in waste collection and recycling, real-time air quality monitoring systems to control pollution levels, and environmental reporting applications that enable active public participation in maintaining environmental cleanliness and health.